Application of MALDI-TOF mass spectrometry in clinical diagnostic microbiology - De Carolis, Elena; Vella, Antonietta; Vaccaro, Luisa; Torelli, Riccardo; Spanu, Teresa; Fiori, Barbara; Posteraro, Brunella; Sanguinetti, Maurizio (The Journal of Infection in Developing Countries, 2014)
Matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF MS) has recently emerged as a powerful technique for identification of microorganisms, changing the workflow of well-established laboratories so that its impact on microbiological diagnostics has been unparalleled. In comparison with conventional identification methods that rely on biochemical tests and require long incubation procedures, MALDI-TOF MS has the advantage of identifying bacteria and fungi directly from colonies grown on culture plates in a few minutes and with simple procedures. Numerous studies on different systems available demonstrate the reliability and accuracy of the method, and new frontiers have been explored besides microbial species level identification, such as direct identification of pathogens from positive blood cultures, subtyping, and drug susceptibility detection.